Base of the pyramid social entrepreneurs: navigating through difficulties and crisis - Cella, Cristina (2022)
The negative socio-economic consequences triggered by Covid-19 pandemic have particularly affected already disadvantaged areas. In this context, Base of the Pyramid (BoP) social entrepreneurs, who embrace social and economic transformation in low-income and vulnerable communities, have experienced both difficulty and resilience along the way. The objective of this study is to have a better understanding of how BoP social entrepreneurs have navigated through the crisis. For this purpose, 10 in-depth, semi-structured interviews were conducted with social entrepreneurs from disadvantaged areas. Research shows that after developing techniques to temporarily secure the financial stability of their ventures, social entrepreneurs saw an opportunity to grow their influence and expand their social mission in smoothing the hardship brought by the pandemic within their communities. Some of the BoP social entrepreneurs were able to take the slow-down of their activities to reflect upon the direction of their organizations and look for the external help of intermediary organizations to give them a direction, a structure and in setting the long-term strategies to foster the desired growth. The analysis has shown that intermediary organizations played a major role in allowing these entrepreneurs to capture the full potential of the opportunities posed by the pandemic.